Die Brüder Augustus Friedrich und Gustav Adolph Vorwerk. Zwei Hamburger Kaufleute - Schröder, Hans Joachim (Mäzene für Wissenschaft, 2009)
The brothers Augustus Friedrich and Gustav Adolph Vorwerk deserve a closer look at their biographies not only because of the generosity with which they supported the Hamburgische Wissenschaftliche Stiftung (Hamburg Scientific Foundation) as donors, but also because of their commercial activities. Together with their father Georg Friedrich Vorwerk - who founded companies first in Hamburg, then in Chile - they pushed forward the Hamburg and Chilean economies. In the suburbs of Klein Flottbek and Nienstedten, the father and the two sons Vorwerk had stately villas built, which to this day are among the remarkable buildings of Hamburg.